2006
DOI: 10.1128/jb.188.3.1071-1080.2006
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracisIsdG, a Heme-Degrading Monooxygenase

Abstract: Bacillus anthracis, the causative agent of anthrax, utilizes hemin and hemoglobin for growth in culture, suggesting that these host molecules serve as sources for the nutrient iron during bacterial infection. Bioinformatic analyses of the B. anthracis genome revealed genes with similarity to the iron-regulated surface determinant (isd) system responsible for heme uptake in Staphylococcus aureus. We show that the protein product of one of these genes, isdG, binds hemin in a manner resembling the heme binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 57 publications
(96 reference statements)
7
131
1
Order By: Relevance
“…Consistent with earlier studies of haem monooxygenases (Kunkle & Schmitt, 2007;Puri & O'Brian, 2006;Skaar et al, , 2006, we observed apparent degradation of the bound haem substrate as (Puri & O'Brian, 2006;Skaar et al, , 2006. This suggests that an additional factor may be needed in vivo to dissociate the degradation product from the protein.…”
Section: A Gaballa and J D Helmannsupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with earlier studies of haem monooxygenases (Kunkle & Schmitt, 2007;Puri & O'Brian, 2006;Skaar et al, , 2006, we observed apparent degradation of the bound haem substrate as (Puri & O'Brian, 2006;Skaar et al, , 2006. This suggests that an additional factor may be needed in vivo to dissociate the degradation product from the protein.…”
Section: A Gaballa and J D Helmannsupporting
confidence: 80%
“…Importantly, members of the HmoA subfamily are found in the human pathogens B. anthracis and Bacillus cereus, where they may play a role in iron acquisition during infection. The overall sequence conservation with B. anthracis and S. aureus IsdG (Skaar et al, 2006), and the retention of most of the known active site residues, suggests a mode of activity similar to IsdG (Reniere et al, 2010). Indeed, both HmoA and HmoB bind haemin with approximately 1 : 1 stoichiometry, and the characteristic haemin absorbance decreases upon addition of reductant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This class of enzymes degrades heme into biliverdin, CO, and iron (6). Furthermore, non-HO homolog heme degrading enzymes have been reported for some bacteria (7)(8)(9). Although heme degradation by this class of weakly similar enzymes has been confirmed by CO production, the precise nature of the resulting products remains controversial (10).…”
mentioning
confidence: 99%
“…HO has been identified in a wide array of organisms, including mammals (1, 2), insects (3,4), and photosynthetic organisms (5,6). Of particular interest, HO is present in many pathogenic bacteria (7)(8)(9)(10), including Neisseria meningitidis (11) and Pseudomonas aeruginosa (12). These pathogenic bacteria have developed sophisticated heme uptake systems that harness the iron from hemecontaining proteins present in the host (13)(14)(15).…”
mentioning
confidence: 99%